Madrasah Hijau Produktif Melalui Optimalisasi Lahan Kosong dan Media Informasi Tanaman - Siti Rhadiatun Mardiah; Suriati Takko; Handrini Juniati; Adriwiniati; Mustika; Risna; St Anisya Darwis; Muhammad Mifta Fausan; Indah Panca Pujiastuti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This community service activity aimed to establish a productive green area as an educational information medium and to enhance students’ active involvement in environmental conservation within the madrasah. The activity was conducted in October 2025 at MTsN 1 Polewali Mandar, involving 50 students and 8 teachers through three stages: planning, implementation, and evaluation. The implementation phase included land preparation, cultivation of horticultural plants (kangkung, pakcoy, mustard greens, and Brazilian spinach), installation of plant identification boards, and the utilization of recycled plastic bottles as planting borders. The results indicated that the vacant land was successfully transformed into a productive green open space, with a plant survival rate of 100%. In addition, there was an increase in students’ participation and environmental awareness, as reflected in their active involvement in planting and maintenance activities.